Soft Skill Competencies Development of Health Workers in Surabaya Indonesia - Wahyunia, Sri; Raharjab, Wildan Taufik; Ibrahimc, Ahmad Zubir (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to know the development of soft skill competencies of health workers in health services at the first level health facility at Community Health centers (PUSKESMAS). Based on data released by the Surabaya city government, the majority of patients’ satisfaction with health services at the Community Health Center in the coastal area has declined. Therefore, it is necessary to map and identify the competencies of health workers and develop competencies based on what is needed. This study used qualitative method and case study research strategy. The reesearcher conducted in-depth interviews with health workers, non-health workers, and patients. This research focused on identifying and developing soft skills competencies in health workers at Community Health Centers. The study results showed they lack communication skills . It is necessary to develop communication skills, such as approaches, patient-centered communication, communication with information technology and cross-cultural communication.